Caring for people with dementia in rural Uganda: qualitative study of caregiving burden experienced by informal and formal caregivers - Herbert E Ainamani; Paul E Alele; Godfrey Z Rukundo; Samuel Maling; Edith K Wakida; Celestino Obua; Alexander C Tsai (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background The rising incidence of Alzheimer's disease among older-age adults worldwide has been accompanied by an increase in caregiving burden. Limited work has examined the lived experiences of both formal and informal caregivers of people living with dementia in low-income countries. # Methods We conducted one-on-one, in-depth qualitative interviews with a purposive sample of 10 informal caregivers and 5 formal caregivers of people living with dementia in Mbarara, Uganda. They were interviewed about their experiences caring for people with dementia until thematic saturation was reached. All interviews were audio recorded, transcribed into English, and thematically analysed. # Results Two primary themes emerged from the data: patient factors influencing caregiving burden (problematic behaviours, such as wandering and aggression) and patient physical health and cognitive deterioration (namely, loss of memory and incontinence). Psychosocial and economic aspects of caregiving burden included financial costs, family conflicts, anxiety, stigma, and substance misuse. # Conclusions Both formal and informal caregivers of people living with dementia experience physical, financial, and psychological stressors. Interventions aimed at reducing these stressors would benefit caregivers as well as improve quality of care for people living with dementia.